Palm fiber composites for aircraft interiors - Khalili, Pooria (2018)
Over the last decades, aircraft manufacturers have produced synthetic fiber thermoset composites to be used for interior components of aircraft. However, the ever increasing dependence on synthetic fibers and thermosetting resin has set the aerospace industry under considerable pressure to reduce its carbon footprint and enhance its sustainable credentials. The unrelenting passion of sustainability has led to an expanding search for eco-friendly fiber reinforced composite from renewable sources. However, there remains a significant challenge to produce palm fiber composite fit for aircraft interiors owing to its ease of combustibility.